PENEGAKAN HUKUM TERHADAP PERTAMBANGAN PASIR BAHAN GALIAN C DI KABUPATEN KUANTAN SINGINGI BERDASARKAN UNDANG-UNDANG NOMOR 4 TAHUN 2009 TENTANG PERTAMBANGAN - Nova Yanti Siburian; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Mining is a part or all phases of activities in the framework of research, management and exploitation of mineral or coal that include investigations, general, exploration, feasibility, construction, mining, processing and refining, transportation and refining, transportation and sales, and post-mining activities. Mining sand quarrying C in Kuantan Singingi an illegal mining that have negative impacts on the environment, public morality and so forth. Therefore, law enforcement agencies Regency Kuantan Singingi attempt to eradicate the illegal sand mining activities. But enforcement of the law by the Law Enforcement Institutions Regency Kuantan Singingi not run effectively and efficiently. This is evident from the data is the increasing number of illegal sand mining from 2013 to 2015. Of the many cases of illegal sand mining in Kuantan Singingi no legal proceedings. The purpose of writing the thesis as follows: first, to find out how the implementation of law enforcement against sand mining minerals C illegal in Kuantan Singingi, secondly, to determine what factors are obstacles in the implementation of law enforcement against Sand Mining Illegal District kuantan Singingi, third, to determine the extent of the role of Local Government in the discipline Regency Kuantan Singingi sand mining quarrying C in Kuantan Singingi.This type of research can be classified in this type of research Sociological, namely direct research on locations or places studied, this study conducted at the Department of Energy and Mineral Resources Regency Kuantan Singingi and police Resort Kuantan Singingi, the research wanted to see the correlation between the law society.From the research, there are three things that can be inferred. First, the implementation of the rule of law against the perpetrators of sand mining extractive C illegally in Kuantan Singingi. Second, obstacles encountered in the implementation of law enforcement against illegal sand mining in Kuantan Singingi them is the lack of public awareness, economic factors, and educational factors. Third, the role of the Regional Government of Regency Kuantan Singingi in mining curb illegal sand quarrying C in Kuantan Singingi of which is to disseminate the relevant community sanctions will be accepted perpetrators of illegal sand mining and the impact of mining on environmental sustainability. Advice writer, first, in carrying out enforcement against illegal sand mining in Kuantan Singingi should be maximized and efforts should be made to arrest the perpetrators of illegal sand mining and not only take steps to prevent it. Second, law enforcement authorities and agencies, Regional Goverment Regency Kuantan Singingi so diligently provide socialization law, so that more people understand and accept written rules made by the competent authorities in order that the higher legal awareness. Third, people should accept all the rules applied by law enforcement agencies and Government Regency Kuantan Singingi in order to achieve security and peace in social life.Keywords: Law Enforcement-Sand Mining-Illegal